2013
DOI: 10.1002/mabi.201300252
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stem Cell Pluripotency in Surface‐Modified Electrospun Fibrous Matrices

Abstract: A previously screened "hit chemistry" (N-[3-(dimethylamino)propyl] methacrylamide) that supports strong attachment and long-term self-renewal of ES cells is selected and grafted to poly(ether sulfone) (PES) fibrous matrices through plasma-induced graft polymerization. The 3D modified fibers exhibit higher cell proliferation and greater expression of pluripotency markers of mouse ES cells than 2D membranes. It is the first demonstration of scaling up an optimal synthetic surface chemistry in 2D using a high thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The use of electrospun substrates on PSC culture has been mostly limited to the induction of differentiation by controlling surface chemistry or the alignment of fibers [49e52]. Nonetheless, Zonca et al recently showed that electrospun PES scaffolds can support the self-renewal of mouse ESCs, demonstrating the feasibility of using electrospun scaffolds as a cell culture substrate for ESCs [23]. Overall, electrospun fibers have shown their potential to support expansion of several types of stem cells.…”
Section: Discussionmentioning
confidence: 98%
“…The use of electrospun substrates on PSC culture has been mostly limited to the induction of differentiation by controlling surface chemistry or the alignment of fibers [49e52]. Nonetheless, Zonca et al recently showed that electrospun PES scaffolds can support the self-renewal of mouse ESCs, demonstrating the feasibility of using electrospun scaffolds as a cell culture substrate for ESCs [23]. Overall, electrospun fibers have shown their potential to support expansion of several types of stem cells.…”
Section: Discussionmentioning
confidence: 98%
“…Polyether sulfone (Mw∼58,000) can be electrospun at 25% w/w in solvents such as DMSO ( Mohammadi Amirabad et al, 2017 ) and NMP ( Yoon et al, 2009 ). But electrospinning of PES in HFIP is possible at concentrations even lower than 9% w/w ( Zonca et al, 2014 ). The surface tension of HFIP is much lower than DMSO and NMP.…”
Section: Discussionmentioning
confidence: 99%
“…The modification process used has been described previously but is reviewed here in brief. The 96-well membrane filter plates were presoaked in Milli-Q water overnight prior to modification. A 100 kDa molecular weight cutoff (MWCO) PES membrane is located and sealed at the base of each well.…”
Section: Methodsmentioning
confidence: 99%